Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Guru - Samsudin, Acep; Prabowo, Budi; Sagala, Polarista Mariani; Br Tarigan, Krisna Melida; Revalina, RR. Viola; Br Ginting, Rahella Ripatiana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This journal aims to examine the influence of education and training on teacher performance. Education and training are key factors in developing teachers' professional competence, which ultimately affects the quality of student education. This journal uses a qualitative approach with document analysis as the data collection instrument.